Some Generalizations Of Recursive Derivates of k-ary Operations - Mileva, Aleksandra; Dimitrova, Vesna (My University, 2018)
We present several results about recursive derivates of kary operations defined on finite set Q. They are generalizations of some binary cases given by Larionova-Cojocaru and Syrbu [7]. Also, we present several experimental results about recursive differentiability of ternary quasigroups of order 4. We also prove that the multiplication group of k-ary quasigroups obtained by recursive differentiability of a given k-ary quasigroup (Q, f) is a subgroup of the multiplication group of the (Q, f).
Keywords: Recursively t-differentiable quasigroups, k-ary operations